The Effect of Morphine on the Incidence of Postoperative Nausea and Vomiting after Strabismus Surgery with Propofol - Mojtaba Rahimi Varposhti; Darioush Moradi Farsani; Masoud Fouladgar (Journal of Pharmaceutical Care, 2018)
Background: Corrective strabismus surgery is associated with moderate pain and a very high incidence of postoperative nausea and vomiting (PONV). In our treatment centers Morphine is used a lot and it’s associated with high incidence of PONV and we have few alternative analgesics. The aim of this study was to compare the incidence of postoperative emesis with intravenous morphine in patients undergoing corrective strabismus surgery with propofol anesthesia with the control group.